KARAKTERISASI GEN PENYANDI PEDIOSIN PAF-11 PADA Pediococcus acidilactici F-11 - Tri Marwati; Nur Richana; Eni Harmayani; Endang S Rahayu (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Pediocin PaF-11 is a ribosomally synthesized antimicrobial peptide produced by Pediococcus acidilactici F-11. The objectives of this research is to find out the location and the nucleotide sequence of gene, which is involved in the production of pediocin PaF-11. Results showed that the pediocin PaF-11 from the cured cell of P. acidilactici F-11 loss the activity, suggested that the pediocin PaF-11 gene was carried in the plasmid. Agarose gel electrophoresis of P. acidilactici F-11 plasmid DNA with marker Î»DNA/HindIII showed that pediocin PaF-11 gene was carried in 12 kb plasmid. Amplification pediocin PaF-11 gene from P. acidilactici F-11 showed that uncured P.acidilactici F-11 culture contain plasmid DNA, indicated by amplification of the papA gene (256 bp). Cured P. acidilactici F-11 culture, plasmid eliminated, indicted by no aplicon DNA detected. This result also suggested that pediocin PaF-11 gene in P. acidilactici F-11 was carried in plasmid. Nucleotide of pediocin PaF-11 encoding gene was sequenced The alignment of that nucleotide sequence showed that pediocin PaF-11 encoding gene have the same sequence with pediocin PA.1 encoding gene in P. acidilactici PAC1.0 and P. acidilactici K10 and pediocin AcH encoding gene in P. acidilactici LB 42-923 and P .parvulus ATO77, and pediocin CP2 in P. acidilactici MTCC 5101.